Daddy Months - Volker Meier; Helmut Rainer (Center for Economic Studies and ifo Institute (CESifo), 2014)
We consider a bargaining model in which husband and wife decide on the allocation of time and disposable income. Since her bargaining power would go down otherwise more strongly, the wife agrees to have a child only if the husband also leaves the labor market for a while. The daddy months subsidy enables the couple to overcome a hold-up problem and thereby improves efficiency. However, the same ruling harms cooperative couples and may also reduce welfare in an endogenous taxation framework.
Keywords: D13; H21; J13; J18; J22; 330; fertility; bargaining; family policy; labor supply